Cell signaling communication within papillary craniopharyngioma revealed by an integrated analysis of single-cell RNA sequencing and bulk RNA sequencing - Xiaoyue Zhu; Yanfei Jia; Zicheng Zhao; Xiaoyu Zhang; Yunlong Zhao; Songbai Gui; Xiu-An Yang (Journal of Translational Medicine)
Abstract Objective This study aims to elucidate the primary signaling communication among papillary craniopharyngioma (PCP) tumor cells. Methods Five samples of PCP were utilized for single-cell RNA sequencing. The most relevant ligand and receptor interactions among different cells were calculated using the CellChat package in R software. Bulk RNA sequencing of 11 tumor samples and five normal controls was used to investigate the pair interactions detected by single-cell RNA sequencing. Results Fibroblasts were not found in ACP, whereas they were detected in PCP. InferCNV revealed high CNV scores for the clusters of epithelial cells and fibroblasts using immune cells as a reference. Epithelial Mesenchymal Transition, Interferon Gamma Response, p53 Pathway, and Estrogen Response Early are pathways commonly shared by fibroblasts and epithelial cells, ranking high in priority. The Wnt signaling pathway and PI3K-Akt signaling pathway play a crucial role in facilitating communication between epithelial cells and fibroblasts. Neutrophils were recognized as the main receivers of incoming signals, with ANXA1-FPR1 and MIF-(CD74 + CXCR2) being identified as the primary signals transmitted from fibroblasts to neutrophils. Conclusion Through analyzing the communication of essential signaling pathways, ligands, and receptors among epithelial cells, fibroblasts, and neutrophils in PCP tumor tissues, we have identified certain molecules with promising prognostic and therapeutic potential.